Morphometric characterization, scrotal and udder measurements of dorper sheep reared in Setiu, Terengganu - Nur Syuhada Ahmad Nordin; Nik Muhammad Syahmi Wan Anuar Shaipudin; Nur Shahira Mohd Saad; Connie Fay Komilus; Azman Azid; Asmad Kari; Kusumawati, Enike Dwi (Penerbit Universiti Kebangsaan Malaysia, 2025)
Dorper sheep are known for their adaptability, high fertility, and meat production capabilities making it a preferred choice among farmers. The Malaysian government has recognized the potential of Dorper sheep and provides support through breed improvement programs, technical assistance, and incentives. However, the lack of knowledge and expertise about Dorper sheep reared in Malaysia poses challenges and hinders their potential for success. Thus, the objectives of this study were to determine morphometric characterization, and testicular and udder measurements of Dorper sheep reared in Malaysia from age 1- to 13-months of age. The study had been conducted at a Dorper farm in Setiu, Terengganu. The data was collected from 49 rams and 49 ewes of Dorper sheep (total n=98) and categorized into five age groups; G1 (1–2-month-old), G2 (4-5-month-old), G3 (6-8-month-old), G4 (10-11-month-old), and G5 (12-13-month-old). The findings indicated that rams and ewes displayed their lowest measurements at G1, while G5 exhibited the highest measurements across all parameters. This observed pattern was primarily attributed to age-related factors, as animals typically experience ongoing physical transformations throughout their maturation and aging process. This study found that body weight (BW) has a positive correlation with body length (BL), wither height (WH), heart girth (HG), hip length (HL), scrotal length (SL), scrotal circumference (SC), teat length (TeL), teat diameter (TD), and distance between udder teat (DBUT). Instead, other variables did not influence the development of ear length (EL) and ear width (EW). The SL was highly correlated with SC (R=0.95), while TeL and TD positively correlated with DBUT (R=0.73 and 0.82, respectively). The description data of the morphometric measurements of the Dorper breed obtained in this study can further be utilized to enhance their management systems and inform breeding programs for the breed, promoting more effective practices.